Development and validation of a grid to evaluate ecosystem services of public urban green spaces in Porto (Portugal) - Vidal, Diogo Guedes (2021)
Cities must be pleasant and healthy spaces able to contribute to ecosystems regeneration and to bring closer Humans and Nature. Contemporary social and environmental issues present big challenges to promoting sustainable and resilient cities. The potential of ecosystem services of the urban green spaces is visible in the regeneration of urban environment, namely in the improvement of environmental and public health and social dimensions. This work presents the development and validation of a grid to evaluate ecosystem services of public urban green spaces. The grid was applied in 25 public urban green spaces in the city of Porto. Statistical tests were performed to evaluate the reliability and consistency of the tool. Results show that the grid is robust and reliable, thus its application is acceptable and could result in potential gains. These include the monitoring of ecosystem services of public urban green spaces to adjust them to citizen’s social and environmental needs, namely if the tool will be adopted by the municipal department of green spaces and infrastructure management of the city of Porto, Portugal.